126Dynamic high density functional substrate mapping improves outcomes in ventricular tachycardia ablation. (18th June 2020) - Srinivasan, N; Garcia, J; Schilling, R J; Ahsan, S; Babu, G; Ang, R; Dhinoja, M J; Hunter, R J; Chow, A W; Lambiase, P D
Abstract: Introduction: Activation and entrainment mapping of VT remains the gold standard for identifying critical sites for ablation of VT, however, this method is limited by poorly tolerated or non-sustained VT. Several substrate guided approaches have been developed, however, outcomes when comparing both methods are similar and overall success can be as low as 47%. A key element in facilitating VT is the presence of dynamic changes within the substrate which may not be evident during sinus rhythm substrate mapping, but may form a critical aspect of the tachycardia mechanism when conduction velocity slows dynamically and tissue refractory periods lengthen. These are rarely studied as part of clinical VT mapping.  Purpose: This study aimed to investigate dynamic substrate changes to local abnormal ventricular activity (LAVA) and late potentials (LP), in relation to critical sites for VT ablation using high resolution mapping of the ventricle with the HD Grid (Abbott, Inc, USA), during short coupled singe extra stimuli from the right ventricle (RV) (Barts Sense Protocol), designed to invoke conduction delay. We hypothesized that the dynamic functional late potential mapping would improve the identification of critical substrate and ablation of these regions would improve outcomes.  Methods: Thirty patients (age 67 +/- 9yrs, 27Male) underwent ablation. Mean ejection fraction was 25% (+/- 10%). Mapping was performed with the AdvisorTM HD Grid multipolar catheter. A bipolar voltage map was obtained during sinus rhythm (SR) and RV Sensed Protocol (SP) single extra pacing. SR and SP late potential (LP) and local abnormal ventricular activity (LAVA) maps were made and compared with critical sites for ablation, defined as sites of best entrainment or pace mapping. Ablation was then performed to critical sites and LP/LAVA identified by the SP. Results: At a median follow up of 10 months 90% of patients were free from symptomatic ATP or ICD shocks. The median area of late potentials across the 30 patients during sinus rhythm was 6.4mm2 during sinus rhythm mapping and 19.3mm2 during sense protocol pacing (p = 0.001). The functional unmasking of LP and LAVA was seen in 26 patients and showed good correlation to critical regions of the VT circuit (sites of best entrainment or pace map). In 24 patients functionally unmasked late potentials were located within 10mm of critical regions within the mapped VT circuit, with a median distance of 8.5mm, compared to 7 patients during sinus rhythm mapping with a median distance of 22mm (p= <0.001). Figure 1 demonstrates and example of the SP, where increased functional LP are seen along the mapped VT isthmus.  Conclusion: Functional LP and LAVA can be unmasked by the sense protocol enabling better delineation of critical regions for VT ablation which may not be visible during sinus rhythm. This unique delineation of functional substrate changes combined with activation or pacemapping may improve outcomes.